Camping Day as a Learning Innovation in Improving Children's Social-Emotional Intelligence in Kindergarten - Rislah Arini; Nurhafizah; Farida Mayar; Serli Marlina (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The increasing global concern regarding children’s declining social-emotional competence within academically dominated early childhood education systems has intensified the demand for innovative pedagogical approaches capable of fostering holistic developmental growth. Despite the growing recognition of experiential learning and Social and Emotional Learning (SEL) frameworks, many kindergarten learning environments continue to rely heavily on classroom-centered instruction that provides limited opportunities for authentic emotional interaction, collaborative engagement, and adaptive social participation. Addressing this gap, the present study investigated the effectiveness of Camping Day activities as a structured experiential learning model for strengthening children’s social-emotional intelligence in kindergarten education. The study employed a quasi-experimental one-group pretest–posttest design involving 60 children aged five to six years from four kindergartens in Kampar Regency, Indonesia. Data were collected through structured observations, semi-structured teacher interviews, and field documentation based on five SEL dimensions, namely self-awareness, self-management, social awareness, responsibility, and relationship skills. Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative findings were interpreted thematically to provide contextual and conceptual depth. The findings revealed a statistically significant improvement in children’s social-emotional intelligence following participation in Camping Day activities, with the mean score increasing from 2.08 to 3.41 (t = 8.73, p < .001). The most substantial improvements were identified in emotional regulation, collaborative responsibility, communication, and peer interaction. The findings further demonstrate that pedagogically mediated experiential outdoor learning creates emotionally meaningful learning ecologies that strengthen children’s adaptive behavior and interpersonal competence through authentic social engagement. This study contributes conceptually by positioning Camping Day as a structured socio-emotional immersion model that extends experiential learning and SEL discourse within contemporary early childhood education while offering a globally relevant pedagogical perspective for fostering holistic child development.